PENGARUH PENGETAHUAN PERPAJAKAN, PEMANFAATAN TEKNOLOGI INFORMASI, SANKSI PAJAK, DAN TINGKAT PENDIDIKAN TERHADAP KEPATUHAN WAJIB PAJAK - Nugraha, R. Andro Zylio; Nurrahman, Arief; Saputri, Agatha; Achmadi, Caesar Rosyad (FEB-UP Press, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are very important pillars in the economy in Indonesia. MSMEs play a very important role in Tax revenue which is the main source of state revenue which has a very large and reliable role for the development of the country, especially in Indonesia. This study uses a quantitative research approach and aims to estimate and test the effect of taxation knowledge, information technology utilisation, tax penalties, and education level on MSME taxpayer compliance in the Special Region of Yogyakarta. Respondents in this study are MSME owners in the Special Region of Yogyakarta (DIY) whose businesses are still actively operating until the research time. The majority of respondents in this study are business actors in the food and beverage sector. The number of questionnaires collected was 183. The sampling technique used in this study was purposive sampling. Data analysis in this study was carried out quantitatively, using smartpls management tools which represented the results and research hypotheses. Based on the test results and discussion carried out, conclusions can be drawn, namely: knowledge of tax regulations (X1), utilisation of information technology (X2), implementation of tax sanctions (X3) and level of education (X4) have an influence on the compliance of MSME taxpayers in the Special Region of Yogyakarta